24 Advances in information delivery for foundation doctor on-call shifts via peer to peer interventions. A QIP (quality improvement project) for service provision. (12th November 2018) - Shah, Jamie; Jones, Victoria; Ghosh, Sandip; Gallacher, Tom; Banks, Louise
Abstract : General medical foundation doctors at the Queen Elizabeth Hospital Birmingham currently cover a complex rota of six different on-call shifts. However from fora and multiple patient safety incidents, issues with shifts clarity were highlighted including: How to access electronic resources. Team roles and responsibilities. Location of handovers. Ensuring patient safety by highlighting weekend reviews. Clarification of cardiac arrest bleeps and areas covered. Differentiation of the requirements between day and night shifts. To review concerns a 12 question survey was created. Doctors (1 st survey n=12, 2nd survey n=9) were asked on a scale of 1–5 how they felt a topic was covered (1 not covered) – 5 (covered very well). 5 Points were consistently highlighted in survey returns: Information not covered in induction/factually inaccurate/omitted from guidelines. Information originated from senior peers only. Minimal role clarification. Documents were complicated and very long. Lack of or difficulty in access to shift documentation. Intervention and results: To intervene a presentation was created, known as 'The Idiots Guide to Foundation On-Calls' ('The Guide').This covered all shift roles, bleeps, responsibilities, timings and handovers.It was delivered at induction, via email and available online. Repeat survey results showed 89% of stakeholders surveyed found 'The Guide' very useful or quite useful, with average confidence score increasing from 2.1 (pre-intervention) to 3.4 (post-intervention). There was a reduction from 67% of poor results (scores of 1 or 2) to 30%, alongside an improvement from 17% of scores 4 or 5% to 40%. Lessons learnt: Involving the key stakeholders in the development of information for the induction processes leads to much better satisfaction and outcomes. Guidelines should be simple, accurate, easy to read, accessible, promoted by others and regularly updated and reviewed by stakeholders.